Agricultural perspectives of climate change induced disasters in Doti, Nepal - Paudyal, Narayan; Khadka, Ram B; Khadka, Ranjana (Journal of Agriculture and Environment, 2013)
Natural disasters are among the major risk factors in aggravating human and livestock lifes as well as agricultural production in most of the developing and poor countries. A community level survey was conducted in Doti district to assess the rural communities perception towards the disasters induced by climate change in agriculture and livestock production and productivity. Discussions with two focal groups, at village level and with district based stakeholders revealed that there is a conceptual difference between the perception of disasters at the government level and the farmers level. Most of the farmers have realized the major disasters of slow onset type (drought and famine) to be more common than the rapid onset type (landslides and floods). There has been a change in the cropping pattern with decreased winter rain and short monsoon rain. The local communities have suffered due to drought which has lead to fewer water holes for animals and less water for irrigation. Farmers have gradually decreased the number of larger ruminants like cattle and buffalo and are inclined towards smaller animals like sheep and goat. Animal diseases as well as insects-pests of crops are also on the rise.